2017
DOI: 10.1371/journal.pone.0171458
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic design of a noise-resistant and efficient closed-loop deep brain stimulation system: A computational approach

Abstract: Advances in the field of closed-loop neuromodulation call for analysis and modeling approaches capable of confronting challenges related to the complex neuronal response to stimulation and the presence of strong internal and measurement noise in neural recordings. Here we elaborate on the algorithmic aspects of a noise-resistant closed-loop subthalamic nucleus deep brain stimulation system for advanced Parkinson’s disease and treatment-refractory obsessive-compulsive disorder, ensuring remarkable performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Solutions to developing fully-closed loop algorithms and optimizing stimulation based on biomarkers have been suggested by computational studies. Recent models have used LFP spectra (beta and gamma power) as feedback-control signals to provide efficient and selective target stimulation in Parkinson's Disease (Karamintziou et al, 2017 ) and essential tremor (Santaniello et al, 2011 ). Using finite element modeling, anatomical models from imaging data can be combined with electrical models to optimize how current is delivered from the DBS electrode (Xiao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Solutions to developing fully-closed loop algorithms and optimizing stimulation based on biomarkers have been suggested by computational studies. Recent models have used LFP spectra (beta and gamma power) as feedback-control signals to provide efficient and selective target stimulation in Parkinson's Disease (Karamintziou et al, 2017 ) and essential tremor (Santaniello et al, 2011 ). Using finite element modeling, anatomical models from imaging data can be combined with electrical models to optimize how current is delivered from the DBS electrode (Xiao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…DBS may normalize firing patterns in the indirect pathway affected by PD , overcoming thalamic inhibition which would further result in MI activation based of the Delong theory of PD . One study utilizing fMRI data with DBS ON and an externalized IPG found activation in the SMA, MI, the premotor cortex and thalamus as compared to DBS OFF, supporting the above presumption .…”
Section: Discussionmentioning
confidence: 89%
“…The current understanding is that the loss of dopaminergic input into the striatum disrupts normal neurotransmitter release, eventually resulting in an increase in inhibition of the thalamus . By altering pulse width, DBS may normalize firing patterns in the indirect pathway affected by PD , overcoming thalamic inhibition. Thus, a greater amount of activation of the thalamus would imply normalization of the basal ganglia pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This would greatly help reduce the amount of charge used and prolong battery life of the DBS stimulators, thus reducing adverse effects and cost over long term. [64] Another potential way of reducing the cost of DBS is through use of refurbished and resterilized pulse generators, an approach that has been attempted by cardiologists in India for pacemakers and implantable cardiac defibrillators. [6566] The safety and efficacy of these techniques have to be studied rigorously before wider clinical application.…”
Section: Resultsmentioning
confidence: 99%